Russia’s Energy Relations with Central and Eastern Europe - Yang, Rui (International Journal of Electric Power and Energy Studies, 2026)
The Russia–Ukraine conflict and subsequent European Union sanctions have reshaped Europe’s energy landscape, transforming energy from a predominantly economic commodity into a central instrument of interstate competition and strategic bargaining. Situated at the intersection of Russia’s traditional sphere of influence and the eastward expansion of the European Union and NATO, Central and Eastern Europe has long constituted a key arena in which Moscow has sought to project influence through energy relations. Existing studies often treat Russian energy assistance in broad and ambiguous terms, thereby overlooking such key dimensions as non-market concessions, political conditionality, and state-led coordination. Drawing on a state-interest perspective and combining historical analysis with contemporary evidence, this article systematically examines the mechanisms through which Russia has structured and utilized energy relations in Central and Eastern Europe. It traces the continuities and transformations from Soviet-era energy arrangements to contemporary Russian practices, arguing that energy has consistently served as a key instrument for maintaining security buffers, extending regional influence, and securing economic returns. However, the mode of engagement has shifted from planned and institutionalized subsidy-based arrangements toward more conditional and flexible practices increasingly coordinated through state-owned enterprises. Based on Russia’s differentiated strategic interests in Central and Eastern Europe, the article develops a threefold typology of partner states: “exceptional partners,” “traditional partners,” and “frontier partners.” Through case studies of Hungary, Serbia, and Moldova, it demonstrates how Russia adopts differentiated energy strategies according to the strategic position of each partner state. These include a pattern of “binding and exchange” toward exceptional partners, “redistribution and binding” toward traditional partners, and “coercion and selective redistribution” toward frontier partners. The study finds that Russia’s energy relations in Central and Eastern Europe are characterized by both continuity and transformation. Building on the Soviet legacy, Russia has increasingly instrumentalized, differentiated, and interest-oriented its energy engagement in order to pursue a dynamic balance among security, political, and economic objectives in the region.